Critical Thinking on the Limitation of Political Functions in Indonesia - Umam, Muhamad Khoerul (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2024)
Ministers or other officials who concurrently hold public and political functions have become a central issue in constitutional studies. Excessive power will make people have the potential to cause abuse of power. This research has a specific objective to analyze and examine the arrangements regarding the limitation of political functions. Methodologically, this research is normative legal research or library research using statutory and conceptual approaches. Data and information obtained through library materials, such as books, journals, and laws and regulations related to research issues. In this research, it is found that some commissioners and directors of state companies or private companies and even ministers or state ministries are involved in concurrent functions that have the potential for abuse of power, and are contrary to Law Number 25 of 2009 concerning Public Services, Law Number 19 of 2003 concerning BUMN, Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition and Law Number 2 of 2011 concerning Amendments to Law Number 2 of 2008 concerning Political Parties. This article is a critique of officials who are involved in concurrent functions as well as providing alternative strengthening in the limitation of functions.